Millimeter Wave Technique for Non-destructive Characterization of Material Homogeneity - Laurinavičius, A.; Kancleris, Ž.; Anbinderis, T.; Martianova, O.; Prishutov, Yu. (Elektronika ir Elektrotechnika, 2006)
Millimeter wave bridge technique for nondestructive material homogeneity characterization is described. The idea of this technique is the local excitation of the millimeter waves in the testing material and the measurement of the transmitted wave amplitude and phase in different places of it, i.e. the material plate is scanned by the beam of the millimeter waves. Same results of the homogeneity measurements for semiconductor and dielectric wafers are presented. The measurement technique sensitivity is discussed. Ill. 6, bibl. 8 (in English; summaries in English, Russian and Lithuanian).